2019
DOI: 10.3847/1538-4357/ab43e3
|View full text |Cite
|
Sign up to set email alerts
|

SN 2017gmr: An Energetic Type II-P Supernova with Asymmetries

Abstract: We present high-cadence UV, optical, and near-infrared data on the luminous Type II-P supernova SN2017gmr from hours after discovery through the first 180 days. SN2017gmr does not show signs of narrow, high-ionization emission lines in the early optical spectra, yet the optical light-curve evolution suggests that an extra energy source from circumstellar medium (CSM) interaction must be present for at least 2 days after explosion. Modeling of the early light curve indicates a ∼500 R e progenitor radius, cons… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 151 publications
2
38
0
Order By: Relevance
“…However, dust formation could also result in a fast-declining tail, and additional effects such as a different radioactivities could affect the decline (Branch & Wheeler 2017), as well as CSM-ejecta interaction, which can contribute to the luminosity at late times (e.g. Andrews et al 2019).…”
Section: Bolometric Light Curvementioning
confidence: 99%
“…However, dust formation could also result in a fast-declining tail, and additional effects such as a different radioactivities could affect the decline (Branch & Wheeler 2017), as well as CSM-ejecta interaction, which can contribute to the luminosity at late times (e.g. Andrews et al 2019).…”
Section: Bolometric Light Curvementioning
confidence: 99%
“…The photometric and spectroscopic follow-up observations of SN2018ivc were obtained and coordinated through Las Cumbres Observatory's Global Supernova Project (GSP; PI: D. A. Howell), a key project to collect densely sampled optical light curves and spectra of nearby and bright SNe (e.g., Andrews et al 2019;Szalai et al 2019).…”
Section: Observationsmentioning
confidence: 99%
“…Such early-time bolometric luminosity excess has been observed in many CCSNe, including the nearby and wellstudied SNe 2017eaw (Morozova et al 2020) and 2018cuf (Dong et al 2020). In some events, like SN 2017gmr (Andrews et al 2019), the excess flux from the CSM can be present without early-time flash ionization features. Morozova et al (2018) demonstrated using light curves of 20 nearby hydrogen-rich (Type II) SNe that early-time excess flux from CSM interaction is a generic feature of this class of CCSNe.…”
Section: Introductionmentioning
confidence: 87%